Context sensitive solutions using interval analysis - Bosurgi, Gaetano; D’Andrea, Antonino; Pellegrino, Orazio (Transport, 2011)
The term ‘Context Sensitive Solutions’ was adopted by the Federal Highway Administration in 1997 and is a synonym of flexibility that allows the designer to balance the safety, mobility and preservation of environmental resources. When the optimal use of design criteria produces an unacceptable solution, the correct application of design value outside the current guidelines with a particular attention to safety and legal risk is needed. In this case, a feasible alternative meets the purpose of design and is considered constructible and maintainable within social, economic and environmental constraints. Unlike in many other countries, road standards in Italy do not permit to work out a simple solution to the problem of flexibility. Specifically, one of the most debated subjects, concerning the items of the Italian Ministerial Decree (MD) 5/11/2001 confer with a designer the possibility of deviating from prescriptive obligations on condition to suggest some appropriate safety analysis. However, it does not indicate any methodology to objectively quantify removal effect from the reference values established by the rule. At this purpose, the paper suggests an analytical instrument for controlling design values outside the current guidelines applying a methodology based on interval analysis, a technique generally used for managing uncertain variables. The procedure applied to designing a planimetric curve has identified the most significant variables and produced some range in which they may be retained acceptable, though outside the limits of the geometric standard. First Published Online: 07 Jul 2011